20 PUBLIC UNIVERSITY HEADS TO CONVENE AND SHARE EXPERTISE ON ASSISTING COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 December 2015 Malaysian public university vicechancellors and rectors will convene here at the Fourth Public Universities ViceChancellors and Rectors Committee (JKNC/R) meeting to discuss and share expertise on how to help the community raise their standard of education and livelihood skills.